2015
DOI: 10.1242/jeb.124859
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII knockdown affects both early and late phases of olfactory long-term memory in the honeybee

Abstract: Honeybees are able to solve complex learning tasks and memorize learned information for long time periods. The molecular mechanisms mediating long-term memory (LTM) in the honeybee Apis mellifera are, to a large part, still unknown. We approached this question by investigating the potential function of the calcium/calmodulindependent protein kinase II (CaMKII), an enzyme known as a 'molecular memory switch' in vertebrates. CaMKII is able to switch to a calcium-independent constitutively active state, providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 87 publications
0
34
0
1
Order By: Relevance
“…The r9 region contains genes for encoding several isoforms of calcium/calmodulin-dependent Serine protein Kinase enzyme (CASK; LOC411347; isoforms identified with BLAST; Fig 6B). CASK interacts with a second Ca 2+ /calmodulin kinase, CaMKII, in a fundamental pathway for memory formation that is shared between humans, fly and honey bees [5456]. We therefore hypothesize that one or both of the divergent haplotypes contain changes to genes that underlie adaptive foraging behaviors at high altitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The r9 region contains genes for encoding several isoforms of calcium/calmodulin-dependent Serine protein Kinase enzyme (CASK; LOC411347; isoforms identified with BLAST; Fig 6B). CASK interacts with a second Ca 2+ /calmodulin kinase, CaMKII, in a fundamental pathway for memory formation that is shared between humans, fly and honey bees [5456]. We therefore hypothesize that one or both of the divergent haplotypes contain changes to genes that underlie adaptive foraging behaviors at high altitudes.…”
Section: Resultsmentioning
confidence: 99%
“…CASK acts together with CaMKII to affect long-term memory formation in honey bees [56,85]. Differences in these genes could contribute to foraging performance in highland bees.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals CaMKII is abundant in the hippocampus, a region of the brain important for memory formulation (Lisman et al, 2002). It has been demonstrated that reduced CaMKII function, via mutation or pharmacological inhibition, leads to impaired learning and long term potentiation in mice (Malinow et al, 1989;Scholl et al, 2015). Drosophila also shows impaired learning and memory following inhibition of CaMKII (Scholl et al, 2015).…”
Section: Creb Signaling Pathways and Memorymentioning
confidence: 99%
“…It has been demonstrated that reduced CaMKII function, via mutation or pharmacological inhibition, leads to impaired learning and long term potentiation in mice (Malinow et al, 1989;Scholl et al, 2015). Drosophila also shows impaired learning and memory following inhibition of CaMKII (Scholl et al, 2015). Knockdown with RNA interference and pharmacological inhibition of CaMKII in honey bee was shown to impair both early and late-long-term memory (Scholl et al, 2015).…”
Section: Creb Signaling Pathways and Memorymentioning
confidence: 99%
See 1 more Smart Citation